ChemInform Abstract: Characterization of MOFs. Part 2. Long and Local Range Order Structural Determination of MOFs by Combining EXAFS and Diffraction Techniques. Issue 36 (9th September 2014) - Borfecchia, Elisa; Gianolio, Diego; Agostini, Giovanni; Bordiga, Silvia; Lamberti, Carlo
Abstract Review: 229 refs.